White-matter-nulled MPRAGE at 7T reveals thalamic lesions and atrophy of specific thalamic nuclei in multiple sclerosis. (July 2020) - Planche, Vincent; Su, Jason H; Mournet, Sandy; Saranathan, Manojkumar; Dousset, Vincent; Han, May; Rutt, Brian K; Tourdias, Thomas
Background: Investigating the degeneration of specific thalamic nuclei in multiple sclerosis (MS) remains challenging. Methods: White-matter-nulled (WMn) MPRAGE, MP-FLAIR, and standard T1-weighted magnetic resonance imaging (MRI) were performed on MS patients ( n  = 15) and matched controls ( n  = 12). Thalamic lesions were counted in individual sequences and lesion contrast-to-noise ratio (CNR) was measured. Volumes of 12 thalamic nuclei were measured using an automatic segmentation pipeline specifically developed for WMn-MPRAGE. Results: WMn-MPRAGE showed more thalamic MS lesions ( n  = 35 in 9 out of 15 patients) than MP-FLAIR ( n  = 25) and standard T1 ( n  = 23), which was associated with significant improvement of CNR ( p  < 0.0001). MS patients had whole thalamus atrophy ( p  = 0.003) with lower volumes found for the anteroventral ( p  < 0.001), the pulvinar ( p  < 0.0001), and the habenular ( p  = 0.004) nuclei. Conclusion: WMn-MPRAGE and automatic thalamic segmentation can highlight thalamic MS lesions and measure patterns of focal thalamic atrophy.